Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1242/jcs.072686
|View full text |Cite
|
Sign up to set email alerts
|

An endophilin–dynamin complex promotes budding of clathrin-coated vesicles during synaptic vesicle recycling

Abstract: Clathrin-mediated vesicle recycling in synapses is maintained by a unique set of endocytic proteins and interactions. We show that endophilin localizes in the vesicle pool at rest and in spirals at the necks of clathrin-coated pits (CCPs) during activity in lamprey synapses. Endophilin and dynamin colocalize at the base of the clathrin coat. Protein spirals composed of these proteins on lipid tubes in vitro have a pitch similar to the one observed at necks of CCPs in living synapses, and lipid tubules are thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 35 publications
5
110
2
Order By: Relevance
“…Dynasore was used to disrupt CME. This pharmacological reagent works by inhibiting the GTPase dynamin (22), which is mainly responsible for the scission of vesicular buds from the plasma membrane (34). It has been suggested that dynamin is also involved in the early stages of CCP formation, serving as both a regulator and integrity monitor (10,35,36).…”
Section: Methodsmentioning
confidence: 99%
“…Dynasore was used to disrupt CME. This pharmacological reagent works by inhibiting the GTPase dynamin (22), which is mainly responsible for the scission of vesicular buds from the plasma membrane (34). It has been suggested that dynamin is also involved in the early stages of CCP formation, serving as both a regulator and integrity monitor (10,35,36).…”
Section: Methodsmentioning
confidence: 99%
“…The cluster-associated protein pool can be mobilized by synaptic activity. Thus, after a period of repetitive stimulation the endocytic proteins partly dissociate from the synaptic vesicles and appear at the plasma membrane in the periactive zone (30)(31)(32). Such protein redistibution has also been observed in live imaging experiments.…”
Section: A Storage Pool Of Endocytic Proteins Is Associated With Synamentioning
confidence: 80%
“…labeled with mCherry should form a complex in the cytoplasm (Ross et al, 2011;Sundborger et al, 2010). Endophilin in the cytoplasm has been found to be a dimer (Ringstad, Nemoto, & De Camilli, 2001;Ross et al, 2011).…”
Section: Applications Of Rics and Nandb To Detect Molecular Complexes Imentioning
confidence: 99%